Language learning and ICTS: Blogs and Forums as mediators in collaborative language learning environments - Carolina Piñeros Pedraza; María Isabel Gutiérrez; Francy Ignory Rico Ruiz (Corporación Universitaria Minuto de Dios, 2009)
This article intends to present some theoretical insights regarding the issue of technology in language classrooms. We present multiple views about e-learning communities and how they entail collaborative learning. Similarly, there is a discussion of Information and Communication Technologies (ICTs) i.e. virtual rooms, blogs and forums as pedagogical tools to promote interaction among students. Finally, we acknowledge process writing as an alternative to encourage real writing in foreign language classrooms.